PENGARUH PENGGUNAAN PORTAL BERITA ONLINE KOMPAS.COM DALAM MEMENUHI KEBUTUHAN INFORMASI SISWA KELAS XII SMK NEGERI 1 KRAS KEDIRI - Rahmawati, Robiul Aulia; Prajawinanti, Arin (Fihris: Jurnal Ilmu Perpustakaan dan Informasi, 2023)
Information needs are the desire in a person to obtain more information to actualize his knowledge and curiosity. The use of mass media is implemented to fulfill information needs. This study was conducted to know the effect of using the Kompas.com online news portal in fulfilling the information needs of grade XII students of SMK Negeri 1 Kras Kediri and knowing the obstacles faced when using the Kompas.com online news portal. The research method used is quantitative with the type of causal correlation, as many as 80 students from grade XII became respondents in this study. Descriptive statistics were carried out to determine the frequency and percentage of respondents' answers. In this study, a simple linear regression test with SPSS 16.0 for windows was used as a data analysis technique. The results of this study obtained a t-count value of 7.396 ≥ t-table of 1.990 with a significance value ≤ 0.05, then Ha is accepted, H0 is rejected. So that the use of the Kompas.com online news portal is proven to have a significant effect in meeting the information needs of class XII students of SMK Negeri 1 Kras Kediri. The results showed that there were several obstacles faced by students when using Kompas.com, such as problematic internet networks, loading pages, and advertisements that often appeared.